Iodine/Sulfinates: Rapid and Convenient Thiolation of Imidazo Heterocycles without Additives - Redon, Sébastien; Mendes, Anne-Sophie; Vanelle, Patrice (Synlett, 2023)
An unprecedented I2/sulfinate thiolating system is described for the sulfenylation of electron-rich heterocycles. This phosphine-free strategy permits simple, efficient, and fast sulfenylation of imidazo heterocycles, anilines, indoles, coumarins, or enaminones.
Keywords: sulfinate; sulfenylation; iodine; microwave heating; heterocycles; thiolation